Stage-dependent shifts in bacterial communities and nitrogen cycling during Pyropia cultivation on the west coast of Korea - Hyo-Ryeon Kim; Ju-Hyoung Kim; Seo-Young Kim; Mi-Jeong Han; Il-Nam Kim (Marine Environmental Research, 2026)

Seasonal variability of surface methane and nitrous oxide under contrasting water–mass influences in the northern East China Sea - Seo–Young Kim; Hui‒Tae Joo; Hyo–Ryeon Kim; Il–Nam Kim (Estuarine, Coastal and Shelf Science, 2026)

Establishment of the East Sea (Japan Sea) Time-series station: an integrated physical–biogeochemical observatory for a climate-sensitive marginal sea - Hui-Tae Joo; Hae-Kun Jung; Jae-Hyun Lim; Jeong-Min Shim; Jeong-Hee Shim; Seo-Young Kim; Hyo-Ryeon Kim; Il-Nam Kim (Frontiers in Marine Science, 2026)
Long-term ocean time-series stations have significantly advanced our understanding of ocean–climate interactions, yet marginal seas remain underrepresented in global observing networks. The East Sea (Japan Sea) provides a valuable natural laboratory, characterized by rapid ventilation, oxygen-rich deep waters, and sensitivity to climate forcing. Recent evidence of weakening deep-water formation and a decline in the uptake of anthropogenic CO 2 in the East Sea underscores the need for sustained, basin-scale observations to assess changes in ventilation, carbon sequestration, and nutrient cycling. Here, we present the establishment of the East Sea Time-series (EaST) station in the Ulleung Basin, with routine seasonal operations beginning in February 2026. The EaST program conducts seasonal measurements of hydrographic, chemical, and biological parameters from surface to deep waters, following international GO-SHIP and OceanSITES standards. All datasets are quality-controlled, archived, and disseminated through the Korea Oceanographic Data Center (KODC). EaST provides a sustained, multidisciplinary time-series framework in the East Sea . By establishing a long-term physical–biogeochemical baseline, the station facilitates sustained monitoring of climate-driven changes in marginal seas and supports integration of regional observations into global ocean observing frameworks.

Investigation of the concentrations and fluxes of potent greenhouse gases (N2O, CH4, and CO2) in the port and harbor seawaters of Jeju Island, Korea - Seo-Young Kim; Hyo-Ryeon Kim; Ju-Hyoung Kim; Jae-Hyun Lim; Il-Nam Kim (Marine Pollution Bulletin, 2025)

Unraveling prokaryotic diversity distribution and functional pattern on nitrogen and methane cycling in the subtropical Western North Pacific Ocean - Satheeswaran Thangaraj; Hyo-Ryeon Kim; Jang-Mu Heo; Seunghyun Son; Jongseong Ryu; Jong-Woo Park; Ju-Hyoung Kim; Seo-Young Kim; Hae-Kun Jung; Il-Nam Kim (Marine Pollution Bulletin, 2023)

Water mass structure determine the prokaryotic community and metabolic pattern in the Korea Strait during fall 2018 and 2019 - Satheeswaran Thangaraj; Hyo-Ryeon Kim; Seo-Young Kim; Hae-Kun Jung; Ju-Hyoung Kim; Il-Nam Kim (Frontiers in Marine Science, 2023)
The Korea Strait (KS) is a crucial marine passage for transporting heat, salt, and materials from the South Sea to the East Sea. The Tsushima Warm Water (TWW) and Korea Strait Bottom Cold Water (KSBCW) are major water masses that flow across the strait, but their effects on prokaryotic communities have been unclear. We used high-throughput sequencing to study the impact of TWW and KSBCW on prokaryotic composition and metabolic changes in the upper (0–50m; UL), middle (50–75m; ML), and bottom (75–150m; BL) layers during the fall of 2018 and 2019. The results showed that the UL had a freshwater influence from Changjiang Diluted Water in 2019, altering prokaryotic compositions and metabolic potentials. The KSBCW in the BL transported new bacterial communities with unique metabolic characteristics. Key genes involved in carbon metabolism had water mass impacts, preferring lower saline and temperature environments, and carbon fixation potential shifted from phototrophs in 2018 to chemotrophs in 2019. Temperature changes induced acclimation processes producing heat- and cold-shock genes/proteins. Our findings indicate that the freshwater influence and KSBCW modified the prokaryotic composition and metabolic function differentially. These results are important in understanding the relationship between water masses and ongoing environmental changes in this understudied region.

An Estimation of Ocean Surface Heat Fluxes during the Passage of Typhoon at the Ieodo Ocean Research Station: Typhoon Lingling Case Study 2019 - Hyo-Jun Bae; Sinil Yang; Taek-Bum Jeong; Ah-Ryeon Yang; Dong-Hyun Cha; Gil Lee; Hwa-Young Lee; Do-Seong Byun; Baek-Min Kim (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Distribution and Production of N2O in the Subtropical Western North Pacific Ocean During the Spring of 2020 - Jang-Mu Heo; Hyo-Ryeon Kim; Sang-Min Eom; Joo-Eun Yoon; JeongHee Shim; Jae-Hyun Lim; Ju-Hyoung Kim; Satheeswaran Thangaraj; Ki-Tae Park; HuiTae Joo; Il-Nam Kim (Frontiers in Marine Science, 2022)
Nitrous oxide (N 2 O) is an important greenhouse gas emitted in significant volumes by the Pacific Ocean. However, the relationship between N 2 O dynamics and environmental drivers in the subtropical western North Pacific Ocean (STWNPO) remains poorly understood. We investigated the distribution of N 2 O and its production as well as the related mechanisms at the surface (0–200 m), intermediate (200–1500 m), and deep (1500–5774 m) layers of the STWNPO, which were divided according to the distribution of water masses. We applied the transit time distribution (TTD) method to determine the ventilation times, and to estimate the N 2 O equilibrium concentration of water parcels last in contact with the atmosphere prior to being ventilated. In the surface layer, biologically derived N 2 O (ΔN 2 O) was positively correlated with the apparent oxygen utilization (AOU) (R 2 = 0.48), suggesting that surface N 2 O may be produced by nitrification. In the intermediate layer, ΔN 2 O was positively correlated with AOU and NO 3 − (R 2 = 0.92 and R 2 = 0.91, respectively) and negatively correlated with nitrogen sinks (N * ) (R 2 = 0.60). Hence, the highest ΔN 2 O value in the oxygen minimum layer suggested N 2 O production through nitrification and potential denitrification (up to 51% and 25% of measured N 2 O, respectively). In contrast, the deep layer exhibited a positive correlation between ΔN 2 O and AOU (R 2 = 0.92), suggesting that the N 2 O accumulation in this layer may be caused by nitrification. Our results demonstrate that the STWNPO serves as an apparent source of atmospheric N 2 O (mean air−sea flux 2.0 ± 0.3 μmol m -2 d -1 ), and that nitrification and potential denitrification may be the primary mechanisms of N 2 O production in the STWNPO. We predict that ongoing ocean warming, deoxygenation, acidification, and anthropogenic nitrogen deposition in the STWNPO may elevate N 2 O emissions in the future. Therefore, the results obtained here are important for elucidating the relationships between N 2 O dynamics and environmental changes in the STWNPO and the global ocean.

Physical Process Controlling the Surface Bacterial Community Composition in the Ulleung Basin of East Sea - Hyo-Ryeon Kim; Jae-Hyun Lim; Ju-Hyoung Kim; Satheeswaran Thangaraj; Il-Nam Kim (Frontiers in Marine Science, 2022)
Although environmental drivers are known to shape the abundance and distribution of bacterial communities in the East Sea, the effects of physical processes have not been directly studied. Here, we aimed to examine the influences of water mass mixing (summer) and eddy circulation (winter) on the surface bacterial communities of the Ulleung Basin (UB), East Sea, based on the metagenomic approach. Overall, 490,087 operational taxonomic units (OTUs) were identified from five stations, and prokaryotic abundance was dominant at all stations in both seasons. Among the prokaryotes, most OTUs were affiliated with Proteobacteria , Cyanobacteria , Flavobacteria , and Actinobacteria during summer and winter. Bacterial communities were found to differ with water masses (Changjiang, Tsushima, and North Korea surface water) and eddy circulation, and were strongly correlated with environmental variables, suggesting specific bacterial community responses with specific seasonal physicochemical parameters. Our investigation indicates that together with distance and environment, advection shapes the UB bacterial community composition, helping us better understand the physical cues related to biological composition in the East Sea. However, further studies are needed to ascertain the role of microbial functional genes along with the advection of oceanographic processes in the East Sea to better understand the regional biogeochemical processes.

Isolation and characterization of polymorphic microsatellite DNA markers for an endangered freshwater fish in Korea, the bull-head torrent catfish Liobagrus obesus - Hyo-Ryeon Lee; Keun-Sik Kim; In-Chul Bang (Conservation Genetics Resources, 2014)

Development and characterization of polymorphic microsatellite marker for an endangered freshwater fish in Korea, Gobiobotia brevibarba - Keun-Sik Kim; Hyo-Ryeon Lee; Sang-Yong Park; Myeong Hun Ko; In-Chul Bang (Conservation Genetics Resources, 2014)